PIFA-Mediated Oxidative Cyclization Reactions of α-Acyl Acrylamides: A Synthetic Route to Substituted Isoxazol-3(2H)-ones - Yuan, Jingwen; Rao, Chitturi Bhujanga; Zhang, Qian; Zhang, Rui; Liang, Yongjiu; Zhang, Ning; Dong, Dewen (Synthesis, 2018)
An intramolecular cyclization of various α-acyl β-amino acrylamides in the presence of PIFA and TFA is described. This transformation features mild reaction conditions, simple execution, high chemoselectivity, and metal catalyst-free oxidation, and thereby, provides not only an alternative protocol for the construction of N–O bond, but also an efficient and straightforward synthesis of substituted isoxazol-3(2H)-ones from readily available α-acyl acrylamides.
Keywords: acrylamides; cyclization; heterocycles; hypervalent iodine reagents; N–O bond formation; isoxazol-3(2H)-ones